Unveiling the Impact of Leadership, Work Discipline, and Compensation on Employee Performance - Wildani, Azka (PRODUKTIF: Jurnal Kepegawaian dan Organisasi, 2023)
The aim of this research is to determine the combined influence of leadership, work discipline, and compensation on employee performance at the East Ciputat Subdistrict Office. This study employs a quantitative approach, focusing on 100 employees of the East Ciputat Subdistrict Office. The sampling technique utilized is Nonprobability sampling, with a sample size of 100 individuals. The data analysis techniques include multiple linear regression analysis, coefficient of determination test, and statistical tests. The results indicate that leadership, work discipline, and compensation do not have a significantly positive impact on employee performance at the East Ciputat Subdistrict Office. When tested together, these three variables - leadership, work discipline, and compensation-collectively explain only 16.8% of the variation in employee performance.